Strategic Entrepreneurship: From Science Laboratory to Commercialization of Disruptive Agri-biotechnology Crop Innovations in Kenya - Stephen Makau Muathe; Odhiambo Antony Benard Kodiwo (Journal of Management Research, 2025)
Commercialization of Agri-biotechnology research outputs has remained low. The government of Kenya has implemented multiple policy frameworks to support the growth of the Agri-biotechnology industry. It has developed an elaborate approval process for Agri-biotechnology innovations. However, despite the huge potential of Agri-biotechnology crop innovations, Bt cotton remains the only product approved in Kenya for commercial cultivation and human use since 2019. This represents a paltry 2.5% of the approved in-house research projects. The industry has not been able to translate its Agri-biotechnology crop research and development into marketed products. Therefore, this study investigated the effect of strategic entrepreneurial mindset, entrepreneurial culture, strategic entrepreneurial leadership, and strategic resource management on the commercialization of Agri-biotechnology crop innovations. The study was founded on four theories: Technology Commercialization Theory, Strategic Entrepreneurship Theory, Knowledge Spillover Theory, and Theory of Traditional Agriculture. A descriptive survey research design was employed. Primary data was collected from 46 scientists from 15 organizations involved in Agribiotechnology research and development in Kenya. The data was analyzed through descriptive statistics, correlation analysis, and multiple linear regression using SPSS version 30. Strategic entrepreneurial practices had a positive and statistically significant effect on the commercialization of Agri-biotechnology crop innovations. This study underscores the critical role of strategic entrepreneurship in the commercialization of Agri-biotechnology crop innovations in Kenya. By fostering an entrepreneurial mindset, cultivating an entrepreneurial culture, and optimizing resource management, organizations can effectively turn their innovations into market-responsive products.